Motif Indonesia Tidak Meratifikasi Convention on Consent to Marriage, Minimum Age for Marriage, and Registration of Marriages - Desy Ramadhani; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations Diponegoro, 2022)
Child marriage is an issue that is of concern to the international community because it is considered to have many negative impacts. Therefore, conventions and organizations that discuss child marriage have started to emerge, one of which is the Convention on Consent to Marriage, Minimum Age for Marriage, and Registration of Marriages. Based on data from UNFPA, Indonesia is the eighth country with the highest child marriage rate in the world. However, with the high rate of child marriage in Indonesia, the Indonesian government has not ratified this convention. In this study, the author seeks to find out the reasons why Indonesia is not ratifying this convention yet. This paper will use cultural relativism concept, patriarchy concept, and rational choice theory.